A review of the Afrotropical Thinophilus Wahlberg, 1844 (Diptera: Dolichopodidae), with the descriptions of ten new species - Grichanov, Igor Ya. (European Journal of Taxonomy, 2023)
Ten new species of Thinophilus Wahlberg, 1844 from the Afrotropical region are described and illustrated: T. saegeri sp. nov. from the Democratic Republic of the Congo, T. medvedevi sp. nov., T. longicercus sp. nov., T. cataractae sp. nov. and T. manambato sp. nov. from Madagascar, T. gallagheri sp. nov. and T. deemingi sp. nov. from Oman, T. sigwalti sp. nov. from Senegal, T. subpalpatus sp. nov. from South Africa, and T. fluvialis sp. nov. from Tanzania. Type material for 13 previously described Afrotropical species is examined. The genus Paralleloneurum Becker, 1902 is newly synonymized with Thinophilus (syn. nov.). As a result, the following new combinations are here established: Thinophilus cilifemoratus (Becker, 1902) comb. nov. and T. pygmaeus (De Meijere, 1916), comb. nov. The following new synonyms are proposed: Thinophilus annulitarsis Parent, 1936 with T. calopus Loew 1852; T. bipunctatus Curran, 1926 and T. maculatus Parent, 1929 with T. indigenus Becker, 1902. New records are given for some known species. Thinophilus argyropalpis Becker, 1910 and T. spinitarsis Becker, 1907 are reported from the Afrotropical Region for the first time. The number of species of the genus, known from continental Africa, Oman, Yemen and Madagascar, has increased to 30. An identification key to 29 Afrotropical species is compiled. Thinophilus versutus Haliday, 1851 and T. cilifemoratus (Becker, 1902), type species of the former genera Schoenophilus Mik, 1878 and Paralleloneurum Becker, 1902, are subsequently also included into the key, because the two species inhabit northern Africa.